PEMBENTUKAN PERATURAN DAERAH DARI INISIATIF DPRD PROVINSI RIAU TAHUN 2015 (Studi Pembentukan Perda No. 10 Tahun 2015 Tentang Tanah Ulayat dan Pemanfaatanya) - Yurita Zahara; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Right of initiative is the inherent right of parliaments in strengthening the legislative function to file the draft regulation in this area is Peraturan Daerah No. 10 Tahun 2015 Tentang Tanah Ulayat dan Pemanfaatannya. Regardless of the dynamics and turbulence in the discussion process, DPRD Riau Province has been able to bring Peraturan Daerah No. 10 Tahun 2015 Tentang Tanah Ulayat dan Pemanfaatannya. This regulation is seen as strategic and aspiration. Therefore, this study aimed to determine the process of establishing legislation initiatives on the communal land. The method used is the method of research with a qualitative approach. The data obtained by interview and documentary data analysis to further analyzed by descriptive analysis method. This study shows that the implementation of the initiative right DPRD Riau Province in the formation of the design and local regulations on the utilization of communal land and take place within a period of time long enough that since projected in 2013 and only completed in 2015. In the process, the Special Committee agencies of communal land the comparative study and public hearings in order to get public response. Along the way, the establishment of a long communal land regulation was caused by constraints include internal constraints such as human resources and political will, while the external constraints that executive dominance (executive heavy) and other assignments. In addition, the Parliament also focus more on supervision and budgeting resulted in flaws in the legislative function. Keywords; Rights Initiative, legislation, the Communal Land